Adverse Outcomes Associated With Stimulator-Based Peripheral Nerve Blocks With Versus Without Ultrasound Visualization. Issue 3 (1st April 2009) - Orebaugh, Steven L.; Williams, Brian A.; Vallejo, Manuel; Kentor, Michael L.
Abstract : Background and Objectives: In this retrospective study, we queried our Quality Improvement database of anesthetic-related complications to evaluate the frequency of noncatheter peripheral nerve block-related adverse occurrences. We hypothesized that adverse complications of nerve blockade are less common when ultrasonography is used in conjunction with peripheral nerve stimulation to guide needle placement, when compared with the sole use of physical landmarks and nerve stimulation. Methods: We queried our departmental Quality Improvement electronic database for adverse outcomes associated with peripheral nerve blocks. Billing records were used to provide the denominator of the total number of blocks using both techniques of neurolocation. The types of blocks considered in this analysis were interscalene, axillary, femoral, sciatic, and popliteal sciatic blocks. The total numbers of complications of nerve blockade with each type of guidance were then compared, as were specific subsets of adverse effects. Results: There were 5436 consecutive peripheral noncatheter block cases (interscalene, axillary, femoral, sciatic, popliteal) during the 28-month period surveyed, with 3290 guided by landmark-nerve stimulation, and 2146 by ultrasound-nerve stimulation. Eight adverse outcomes occurred among patients having blocks guided by landmark-nerve stimulation technique, including 5 seizures and 3 nerve injuries. There were no such occurrences in the ultrasound-nerve stimulation group. When comparing the 4 brachial plexus block-related seizures that occurred with landmark guidance versus none with ultrasound guidance, the associated risk of seizures reached statistical significance ( P = 0.044 by Fisher exact test). There was no difference between the 2 groups in the number of seizures occurring with lower extremity blocks, or in the frequency of neurologic injury. Conclusions: High-definition ultrasonography offers potential advantages in the administration of peripheral nerve blockade. The significant difference in major central nervous system local anesthetic toxicity observed in this study supports the use of ultrasound guidance in conjunction with peripheral nerve stimulation to provide brachial plexus peripheral nerve blockade in an academic, ambulatory anesthesia practice.